Phase I study of cisplatin and nanoparticle albumin‐bound‐paclitaxel combined with concurrent radiotherapy in locally advanced esophageal squamous cell carcinoma - Hui Jiang; Qiaoqiao Li; Baoqing Chen; Mian Xi; Kanjiebubi Makelike; Shiliang Liu; Yonghong Hu; Yujia Zhu (Cancer Medicine, 2023)
Abstract Background This phase I study aimed to assess the safety, dose‐limiting toxicity (DLT), maximum tolerated dose (MTD) and preliminary effect of nanoparticle albumin‐bound (nab)‐paclitaxel in combination with concurrent chemoradiotherapy in patients with locally advanced esophageal squamous cell carcinoma (ESCC). Methods Patients with locally advanced ESCC who were ineligible or refused surgery were enrolled. Nab‐paclitaxel (60 mg/m2, 75 mg/m2, and 90 mg/m2) and cisplatin (25 mg/m2) were administered intravenously weekly on days 1, 8, 15, 22, and 29 on the basis of the 3 + 3 dose escalation method. The total dose of radiation was 50–64 Gy. The primary endpoint was the safety of chemotherapy. Results The study enrolled 12 patients across three dose levels. No treatment‐related deaths occurred. One patient in the 60 mg/m2 dose level occurred dose‐limiting Grade 3 febrile neutropenia. No DLT was found in the 90 mg/m2 dose level thus the MTD was not reached. The phase II study's recommended dose was 75 mg/m2 based on the available preclinical and clinical data including pharmacokinetics, pharmacodynamics, efficacy, and toxicity. The frequent hematologic toxicities were leukocytopenia (Grade 1–2 of 66.7% and Grade 3–4 of 33.3%), neutropenia (Grade 1–2 of 91.7% and Grade 3–4 of 8.3%). Nonhematologic toxicities were mild and manageable. Overall response rate (ORR) of all patients achieved 100%. Conclusions Weekly schedule of cisplatin and nab‐paclitaxel in combination with concurrent radiotherapy showed manageable toxicities and promising antitumor activity in patients with locally advanced ESCC. The recommended dose of nab‐paclitaxel for further studies is 75 mg/m2.